A case of keloid - Venkataramana Vannala; Nazargi Mahabob; Senthilnathan Radhakrishnan; Sambavi Anbuselvan (Wolters Kluwer Medknow Publications, 2021)
Keloids are unorganized proliferation of fibrous tissue, usually arising from a site of injury, due to an aberrant healing process. Clinically, it presents as an ugly scar tissue on the skin and shows genetic predilection. They cause esthetic, physical, and psychological disturbances in the affected individuals. Such patients require special precautions during the normal surgical procedures. Keloid treatment is prone to a high degree of resistance and recurrence. In this article, one such a case is reported along with a review of the literature discussing the nature of the lesion, treatment options, and the recommended precautions.